2017
DOI: 10.1002/app.46106
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐rich porous polyaminal network as a platform for iodine adsorption through physical and chemical interaction

Abstract: A series of nitrogen-rich porous polyaminal networks (PANs) with five different linkages were prepared through a facile route from cost-effective starting materials. Each structural unit bears a different number of phenyl and pyrrolyl rings, which are found to be useful for iodine uptake through a physical adsorption mechanism. The PAN3 bearing the 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BDP) units, which could adsorb iodine by both physical and chemical interaction, achieves an efficient iodine capacity u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Iodine uptake [88] PAN3 Phenyl and pyrrolyl rings Iodine uptake [89] MelPOP-2 and TatPOP-2 50.5 and 36.5 Phosphorus and nitrogen heteroatoms, and p-π conjugated units Iodine uptake [90] COF-DL229 1762 π-conjugated pore walls Iodine uptake [91] CalPOF Azo groups, macrocyclic π-rich cavities and phenolic units Iodine uptake [92] PHF-1-Ct Positive charge and nitrogen Iodine uptake [93] PSIFs Imine groups and silsesquioxane Iodine uptake [94] HCMP-1, 2, 3, 4 Amine groups Iodine uptake [95] Azo-Trip 510. different mechanisms of separation, we will summarize the novel porous polymers in both adsorption and membrane separation area. As a kind of traditional ion-exchange resins, crosslinked polystyrene-based resins and their carbonized derivatives have found wide applications in material adsorption, extraction, and analysis.…”
Section: Ahcp-1 Sodium Tetraphenylboronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine uptake [88] PAN3 Phenyl and pyrrolyl rings Iodine uptake [89] MelPOP-2 and TatPOP-2 50.5 and 36.5 Phosphorus and nitrogen heteroatoms, and p-π conjugated units Iodine uptake [90] COF-DL229 1762 π-conjugated pore walls Iodine uptake [91] CalPOF Azo groups, macrocyclic π-rich cavities and phenolic units Iodine uptake [92] PHF-1-Ct Positive charge and nitrogen Iodine uptake [93] PSIFs Imine groups and silsesquioxane Iodine uptake [94] HCMP-1, 2, 3, 4 Amine groups Iodine uptake [95] Azo-Trip 510. different mechanisms of separation, we will summarize the novel porous polymers in both adsorption and membrane separation area. As a kind of traditional ion-exchange resins, crosslinked polystyrene-based resins and their carbonized derivatives have found wide applications in material adsorption, extraction, and analysis.…”
Section: Ahcp-1 Sodium Tetraphenylboronsmentioning
confidence: 99%
“…The enhanced adsorption performance can be realized by presetting N heteroatomic units, such as amine, imine, pyrrole, and other N containing rings. [88][89][90][92][93][94][95][96][97][98]100] The π-conjugated structure in aromatic frameworks also increased the adsorption affinity to iodine species. [88,[90][91][92]97,99] Moreover, other heteroatoms (P, S, and B), [87,90,100] phenolic groups, [92] and charged groups [86,93] are also beneficial to elevate the uptake performance.…”
Section: Radionuclide Extractionmentioning
confidence: 99%
“…It has been reported that iodine sequestration efficiency is a function of several structural properties of the adsorbent including surface area, pore size, specific high-affinity binding sites, polar groups, and conjugated units. Thus, increasing the affinity of the host to iodine, in addition to enhanced surface area, can have tremendous effect on iodine capture 4 , 5 , 14 , 15 . Materials like activated carbon, silica, silver-doped zeolites, chalcogenide aerogels, and microporous polymers have been reported to show good adsorption capacities for radioiodine 5 , 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Pan et al developed N-and S-rich covalent organic framework (COFs) possessing high iodine uptake of 276 wt.% 29 . Triazine-based conjugated polymers have also been reported to have respectable iodine uptake, presumably due to their nitrogen-rich nature 4,15,[30][31][32][33][34][35] . The high number of basic nitrogen sites on the triazine unit enhances the uptake capacity that originates from the formation of charge-transfer complexes of nitrogen-iodine (donor-acceptor) systems formed during iodine adsorption on the polymers 7,12,15,36 .…”
mentioning
confidence: 99%
See 1 more Smart Citation